Assessing the impacts of oil spillage from ships on coastal environment of Bangladesh: means for response and mitigation - Karim, Iqbal (BRAC University, 2011)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2009.